2022
DOI: 10.1155/2022/5463134
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin 5 Plays an Important Role in Promoting Ferroptosis in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease in the elderly, which is related to brain iron metabolism disorders. Ferroptosis is a newly discovered iron-dependent programmed cell death mode, which has been considered an essential mechanism of PD pathogenesis in recent years. However, its underlying mechanisms have not been fully understood. In the present study, the PD rat model and PD cell model were induced by 6-hydroyxdopamine (6-OHDA). The results showed that the expression of Sorting Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The Drp1 downregulation and upregulation have been shown to be influence mitochondrial fission and fusion process along with bidirectional relationship between mitochondrial ROS signaling. Drp1 overexpression/upregulation in certain cancer cells cause mitochondrial fragmentation, energy deficiency and increase in mitochondrial ROS [62], [63]; whereas Drp1 knock-down showed decreased mitochondrial fission [64]. In contrast, another study showed that Drp1 knockdown induces mitochondrial dysfunction, impairs mitochondrial respiration and cause upregulation of oxidative stress markers [65].…”
Section: Discussionmentioning
confidence: 99%
“…The Drp1 downregulation and upregulation have been shown to be influence mitochondrial fission and fusion process along with bidirectional relationship between mitochondrial ROS signaling. Drp1 overexpression/upregulation in certain cancer cells cause mitochondrial fragmentation, energy deficiency and increase in mitochondrial ROS [62], [63]; whereas Drp1 knock-down showed decreased mitochondrial fission [64]. In contrast, another study showed that Drp1 knockdown induces mitochondrial dysfunction, impairs mitochondrial respiration and cause upregulation of oxidative stress markers [65].…”
Section: Discussionmentioning
confidence: 99%
“…The study of ferroptosis mechanisms in PD neurons has received increasing attention [21] [22], in the PD model, GPX4 expression and GSH/GSSG ratio decreased; MDA concentration and ferrous ion concentration increased, suggesting that lipid peroxidation and ferroptosis of neurons do occur in the PD pathological. KIF5A is neuron-speci c and is a critical molecule in axonal transport.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 6-OHDA-mediated changes in the expression of GPX4 were further aggravated upon co-treatment of PC12 cells with 6-OHDA and erastin (1 µM, 24 h) (more pronounced decrease in GPX4 expression when compared to cells treated only with 6-OHDA). In addition, the ferroptosis inhibitor Fer-1 (25 µM, 24 h) was capable of counteracting 6-OHDA-mediated ferroptosis, significantly inhibiting 6-OHDA-mediated decrease in GPX4 expression [ 115 ].…”
Section: Models To Study Ferroptosis In Neurodegenerationmentioning
confidence: 99%
“…Furthermore, SNCX5 expression levels were significantly increased in PD rats, suggesting that 6-OHDA-mediated abnormal increases in the SNX5 expression levels and ferroptosis may, potentially, induce the development of PD. Thus, given its ability to induce ferroptosis in PD, SNX5 might represent an alternative target to explore potential therapeutical approaches for PD treatment [ 115 ].…”
Section: Models To Study Ferroptosis In Neurodegenerationmentioning
confidence: 99%